Evaluation of Inflammatory Cytokines (IL-6, TNF-α, IL-10) and Upper Airway Obstructive Factors in Patients with Obstructive Sleep Apnea and Their Association with Cardiometabolic Risk - Sajjad Ghani, Nishat Afroz, Hameedullah Achakzai, Waqas Qurshi, Ramsha Aamir, Saima Jatoi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder characterized by recurrent episodes of upper airway obstruction during sleep, resulting in intermittent hypoxia, oxidative stress, and systemic inflammation. Increasing evidence suggests that inflammatory cytokines play a crucial role in the pathophysiology of OSA and its associated cardiometabolic complications. Objective: To evaluate serum levels of inflammatory cytokines (IL-6, TNF-α, and IL-10) and upper airway obstructive factors in patients with obstructive sleep apnea and to determine their association with cardiometabolic risk. Methods: This cross-sectional study was conducted at Nishtar Hospital, Multan, and Isra University Hospital, Hyderabad, Pakistan, from June 2022 to February 2023. A total of 100 participants were included, comprising patients diagnosed with obstructive sleep apnea and healthy controls. Clinical evaluation included demographic characteristics, body mass index, neck circumference, and upper airway examination to identify structural obstructive factors. Serum inflammatory cytokines including IL-6, TNF-α, and IL-10 were measured using the enzyme-linked immunosorbent assay (ELISA) method. Cardiometabolic risk parameters including fasting blood glucose, lipid profile, and blood pressure were also assessed. Statistical analysis was performed using SPSS version 25, and a p-value <0.05 was considered statistically significant. Results: Patients with obstructive sleep apnea demonstrated significantly higher levels of IL-6 and TNF-α compared with healthy controls, whereas IL-10 levels were significantly reduced. OSA patients also exhibited higher body mass index, neck circumference, fasting blood glucose levels, and dyslipidemia, indicating increased cardiometabolic risk. Upper airway obstructive factors such as tonsillar hypertrophy, nasal obstruction, elongated uvula, and soft palate enlargement were significantly more prevalent among OSA patients. Furthermore, elevated pro-inflammatory cytokine levels showed positive correlations with obesity, hypertension, and metabolic abnormalities. Conclusion: The study demonstrates that obstructive sleep apnea is associated with increased systemic inflammation and upper airway structural abnormalities, which contribute to elevated cardiometabolic risk. Measurement of inflammatory cytokines such as IL-6 and TNF-α may serve as useful biomarkers for identifying patients at risk of metabolic and cardiovascular complications associated with OSA. Keywords: Obstructive sleep apnea, inflammatory cytokines, IL-6, TNF-α, IL-10, cardiometabolic risk, airway obstruction, systemic inflammation.